Stilìstičnì studìï movoznavcìv harkìvsʹkoï fìlologìčnoï školi 20–30 rr. HH st. - Čeremsʹka, Olʹga (Stylistyka, 2019)
The article focuses on the concept of historical memory on the basis of the Ukrainian linguistics ofthe 1920s and 1930s. The aspects of the scientific work of linguists of the Kharkiv Philological School (O. Vetukhov, M. Yogansen, O. Kurylo, M. Nakonechnyi, K. Nymchynov, V. Simovych, O. Synyavskyi, S. Smerechynskyi, M. Sulyma, B. Tkachenko, О. Finkel), who were in creative interaction with the Slavic and European scientific circles, are characterised; the influence of the ideas of the Prague linguistic circle, in particular its structural-semantic paradigm, on the directions of scientific research of Ukrainian linguists during the mentioned period is noted. Attention is focused on the main achievements of Ukrainian linguistics in the field of stylistics. The work of O. Kurylo Attention on the modern Ukrainian literary language (1920) is analysed in view of the terminology apparatus of stylistics, including theoretical and methodological principles of Ukrainian and Slavic linguistics in general. The stylistic advisers of M. Gladkyi, which highlight the cultural aspects of journalism and literature, and peculiarities of word-formation in the language of the press and fiction, are discussed. The work Ukrainian phrase. Short Sketches (1928) by M. Sulyma, devoted to issues of stylistic morphology and stylistic syntax is investigated as well as the terminology of stylistics used in the work of S. Smerechynskyi Essays on the Ukrainian syntax (in connection with phraseology and stylistics) (1932); M. Yogansen’s scientific discoveries Elementary laws of versification (1922) and How the narrative is constructed. Analysis of Prose Samples (1927) as well as O. Finkel’s: A Brief Introduction to Theoretical Stylistics (1927), L. Bulakhovsky’s The Basics of Linguistics (1931–1932) are scrutinised. The course of B. Tkachenko’s Essay of Ukrainian Stylistics (Kharkiv, 1929–1930?), created under the influence of French stylistics by S. Bally is noted, in which for the first time in Ukrainian linguistics, the necessity of studying stylistics as a separate educational discipline was proved, its purpose and task were articulated, and conceptual apparatus outlined; the essence and nature of the interrelations of the literary language with individual and folk-colloquial language are investigated.